1980
DOI: 10.2337/diab.29.7.501
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Study of Risk Factors for Retinopathy and Nephropathy in Diabetes

Abstract: Indexes of retinopathy and nephropathy were studied in a large population of diabetics using standardized methods. In each of 973 subjects, more than 100 other variables were also measured: this made It possible to take into account many confounding factors when we examined the relationships of these variables to microangiopathy. The most powerful risk factor for microangiopathy was duration of diabetes, but frequency of both retinopathy and nephropathy was impressively related to the level of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
102
2
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(120 citation statements)
references
References 0 publications
14
102
2
1
Order By: Relevance
“…Trivial trends occur in the reverse direction for BMI and proteinuria, an association which may in part be secondary to fluid retention accompanying renal impairment. The association of SVDE with lower BMI confirms a recent report on retinopathy in Oklahoma Indians [32]. Greater prevalence of retinopathy in the more severely hyperglycaemic, thinner or insulin-dependent diabetics may exist, and further analysis is necessary before conclusions can be drawn.…”
Section: Small-vessel Disease Prevalencesupporting
confidence: 69%
“…Trivial trends occur in the reverse direction for BMI and proteinuria, an association which may in part be secondary to fluid retention accompanying renal impairment. The association of SVDE with lower BMI confirms a recent report on retinopathy in Oklahoma Indians [32]. Greater prevalence of retinopathy in the more severely hyperglycaemic, thinner or insulin-dependent diabetics may exist, and further analysis is necessary before conclusions can be drawn.…”
Section: Small-vessel Disease Prevalencesupporting
confidence: 69%
“…On the other hand, Weber et al found that serum triglycerides were strongly associated with degree of retinopathy in children and adolescents with diabetes mellitus type 1 (Weber et al 1986). Other studies (Eckel et al 1981;West et al 1980) support the latter finding with a relationship between higher levels of triglycerides and more severe retinopathy. In our study we found serum triglycerides to correlate rather weakly, although significantly, to degree of retinopathy with the highest levels found in the group of diabetic subjects with proliferative retinopathy.…”
Section: Discussionmentioning
confidence: 76%
“…Serum cholesterol levels were in some studies found to correlate to more severe retinopathy (Dornan et al 1982;Eckel et al 1981;Mouton & Gill 1988 ;Scanu & Fless 1990;Weber et al 1986) while in other studies such a relationship was not found (Weber et al 1986;West et al 1980). Dornan et al (1982) measured serum lipid levels in small groups of insulin-dependent diabetic patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In IDDM, lipid profile disturbances (21), hypertension and/or a family history of hypertension (22,23), smoking and high body mass index have also been associ-ated with DN (24,25). Despite the considerable contribution of NIDDM to renal replacement therapy (25,26), studies on risk factors in these patients are less common (27). In Brazil, a cross-sectional study evaluated characteristics of NIDDM patients who were proteinuric (28), but epidemiological data on risk factors for ESRF are not available.…”
Section: Introductionmentioning
confidence: 99%